1996
DOI: 10.1097/00003246-199605000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide inhalation decreases pulmonary platelet and neutrophil sequestration during extracorporeal circulation in the pig

Abstract: Apart from the effects of nitric oxide on central hemodynamics in this model, the scintigraphic findings indicate an in vivo effect of nitric oxide on the accumulation of platelets and neutrophils in the lungs, probably due to inhibition of the adhesion and/or aggregation of these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 22 publications
1
11
1
1
Order By: Relevance
“…40 In the present study, the platelet and white blood cell counts remained stable during NO administration, most likely excluding a relevant leukocyte or platelet sequestration. 41,42 A decrease in platelet fibrinogen binding was observed after administration of various NO-releasing compounds in vitro and in vivo. 26,43,44 Furthermore, the increase in GP IIb/IIIa receptor expression was abolished during administration of S-nitrosoglutathione and nitroglycerin in patients with unstable angina and acute myocardial infarction 21 and during percutaneous transluminal coronary angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…40 In the present study, the platelet and white blood cell counts remained stable during NO administration, most likely excluding a relevant leukocyte or platelet sequestration. 41,42 A decrease in platelet fibrinogen binding was observed after administration of various NO-releasing compounds in vitro and in vivo. 26,43,44 Furthermore, the increase in GP IIb/IIIa receptor expression was abolished during administration of S-nitrosoglutathione and nitroglycerin in patients with unstable angina and acute myocardial infarction 21 and during percutaneous transluminal coronary angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, results of an animal study, demonstrating an inhibition of platelet and leukocyte sequestration in the lungs, suggested that inhaled NO can improve the pulmonary microvasculature during extracorporeal circulation (11).…”
Section: Discussionmentioning
confidence: 99%
“…A biphasic effect on the leukocyte oxidant burst with an inhibition at high NO concentrations has been described by others (8). Additional data suggest that leukocyte function is also inhibited during NO inhalation because up to 70 ppm of inhaled NO inhibited the aggregation and migration of polymorphonuclear leukocytes (PMNs) in an animal model of lung transplantation and sepsis (9,10) and pulmonary platelet and neutrophil sequestration during extracorporeal circulation in the pig (11).…”
mentioning
confidence: 99%
“…Effects of NO on coagulation NO interferes with platelet and leukocyte functions, 31 fibrinolysis, 32 restenosis, 33 and reperfusion injury 34 by inhibiting expression of adhesion molecules at leukocyte surfaces and by activating sGC, which lead to rapid increase in platelet cGMP and inhibition of platelet aggregation. NO also inhibits vascular smooth muscle cell proliferation, leading to decreased neointimal hyperplasia.…”
mentioning
confidence: 99%